Contribution to the knowledge of Neoperla (Plecoptera: Perlidae) from Hainan Province of China - Chen, Zhi-Teng; Du, Yu-Zhou (Zootaxa, 2016)
The species of the perlid genus Neoperla are reviewed from Hainan Province, China. Three species of Neoperla, N. minuta sp. nov., N. wuzhishana sp. nov., and N. sexlobata sp. nov. are described from this island province and compared with other taxa. A provisional key is presented to the known Neoperla males from Hainan Province.